Thomas & friends. All engines go : race for the Sodor Cup [videorecording (DVD)] - Awdry, Christopher (NCircle Entertainment, 2022)
Kana and Thomas will discover that it takes teamwork to become the best racers they can be, but is it enough to defeat the international champions and win the Sodor Cup?